THE INFLUENCE OF COMPANY CHARACTERISTICS ON MARKET REACTION, WITH QUALITY OF VOLUNTARY DISCLOSURE AS INTERVENINGVARIABLE (MANUFACTURING COMPANIES LISTED ON IDX PERIOD 2012-2016) - Rahimah, Zulaikha; Diantimala, Yossi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The objectives of this research are to examine the influence of company characteristics includes age of company, size, leverage, profitability, liquidity and growth on market reaction with quality of voluntary disclosure as intervening variable on manufacturing company listed on Indonesia Stock Exchange in 2012-2016. The research sample is the manufacturing company listed on Indonesia Stock Exchange in 2012-2016. The sample are collected using purposive sampling method and resulted 2012 and 2013 is as much as 113 companies, 2014 is 112 companies, 2015 as much as 107 companies and 2016 as much as 41 companies. In summarize the total observation for 5 years are 486. The data type used is secondary data obtained from the annual report of a company that listed on IDX. Then, the method used is path analysis. The research results show that simultaneously age of company, size, leverage, profitability, liquidity and growth have no influence on quality of voluntary disclosure, nevertheless the relation partially show that (1) age has no influence on quality of voluntary disclosure, (2) size has negative influence on earnings persistence, (3) leverage has no influence on quality of voluntary disclosure, (4) profitability has no influence on quality of voluntary disclosure, (5) liquidity has no influence on quality of voluntary disclosure, and (6) growth has no influence on quality of voluntary disclosure. Next results show that quality of voluntary disclosure has influence on market reaction (abnormal return), nevertheless the relation partially show that quality of voluntary disclosure has negative but significant influence on abnormal return. Mediation result shows that age, size and liquidity that mediate by quality of voluntary disclosure on market reaction. Meanwhile, quality of voluntary disclosure is not mediating the influence of leverage, profitability and growth on market reaction (abnormal return).